2017
DOI: 10.1108/imr-07-2014-0235
|View full text |Cite
|
Sign up to set email alerts
|

The influence of relational capability and marketing capabilities on the export performance of emerging market firms

Abstract: Purpose Drawing on the resource-based view, the purpose of this paper is to focus on the influence of relational capability and marketing capabilities on export performance. The study also examines the interaction effects of relational capability on the marketing capabilities – export performance relationships. Design/methodology/approach A stratified random sample of 1,047 exporting firms was approached. Survey data were collected from 333 Vietnamese exporting firms and analysed using hierarchical moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 74 publications
7
94
0
9
Order By: Relevance
“…Consequently, the relational view advocated that when vertical power asymmetries exist among the collaborating business partners, the potential for extreme knowledge utilization by major and stronger partners is generally offset by the complementarities of the weaker partners (Obayi, Koh, Oglethorpe, & Ebrahimi, 2017). Therefore, relational capability has been established to positively influence marketing intelligent gathering (Pham et al, 2017), enhance firm's cultural orientation (Luvison & de Man, 2015), capability for the co-value creation and information sharing (Ngugi et al, 2010), and expedite the conversion of customer knowledge into specific market product (Sánchez-Gutiérrez, Cabanelas, Lampón, & González-Alvarado, 2018):…”
Section: Relational Capability and Learning Capabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, the relational view advocated that when vertical power asymmetries exist among the collaborating business partners, the potential for extreme knowledge utilization by major and stronger partners is generally offset by the complementarities of the weaker partners (Obayi, Koh, Oglethorpe, & Ebrahimi, 2017). Therefore, relational capability has been established to positively influence marketing intelligent gathering (Pham et al, 2017), enhance firm's cultural orientation (Luvison & de Man, 2015), capability for the co-value creation and information sharing (Ngugi et al, 2010), and expedite the conversion of customer knowledge into specific market product (Sánchez-Gutiérrez, Cabanelas, Lampón, & González-Alvarado, 2018):…”
Section: Relational Capability and Learning Capabilitymentioning
confidence: 99%
“…Equally, to determine how SMEs firm upgrade its knowledge and skills about the physical environment in a unique way and transforming the knowledge into instructions and designs for efficient creation of desired performance, technological capability was measured with 11 items adapted from the study of Wang et al (2006). Furthermore, the nine items used to measure relational capability in this study were adapted from Pham et al (2017), to ascertain how SMEs develop effective collaboration with strategic partners to access information and resource which cannot be independently provided to effectively satisfy the market needs. However, learning capability was measured with seven items adapted from the work of Hailekiros and Renyong (2016), which evaluates the degree of SMEs commitment toward the promotion and support of the firm's learning process to directly enhance performance and influence other capabilities to improve competitive advantage and performance.…”
Section: Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, Pham et al (2017) investigated levels of conditions for marketing analysis and marketing capability using survey data set from a sample of 311 Vietnamese firms. Multiple regression analysis was used and the findings revealed that except for responsiveness to macro environment, marketing capability may not have a positive effect on firm performance.…”
Section: Discussionmentioning
confidence: 99%